Dynamic behavior of an agricultural power take-off driveline for rattle noise reduction: Part 2. Experimental analysis of rattle noise effect according to spline tolerance level. (June 2022) - Choi, Chanho; Ahn, Houngjong; Yu, Jihun; Park, Young-Jun; Lee, Jinwoong; Park, Jinkam; Kim, Su-chul
Highlights: Gear rattle noise in power take-off drivelines is influenced by spline tolerance. Jumping phenomenon occurs at lower rotation speed as increasing tolerance. As the tolerance increases, the collision periodicity disappears. Collisions are irregular beyond a threshold tolerance, causing large rattle noise. Abstract: Agricultural tractors comprise power take-off (PTO) drivelines, which that transmits engine power to the outside for various agricultural work, and various mechanical components are connected by spline couplings with tolerances. Dynamic behavior of the spline couplings causes a jumping phenomenon where the rotation speed fluctuation amplifies and then rapidly decreases. This paper experimentally examined the effects of spline tolerance on the dynamic behavior and PTO gear rattle noise for four different spline tolerance levels. For the fit tolerance (0.1 mm), no jumping was observed. For increasing tolerance levels of 0.5, 0.9, and 1.3 mm, the jumping rotation speed decreased to 920, 890, and 880 rpm, respectively. With increasing tolerance, both the rotation speed fluctuation and noise level immediately before jumping increased gradually. Furthermore, for the specimen with tolerance levels of 1.3 mm(type D), a transient range was observed in which the dynamic behaviors before and after jumping were mixed and rotation speed fluctuation and sound pressure level showed large deviations from their respective average values.